Transformasi Komunikasi Antarbudaya di Perbatasan Indonesia–Timor Leste Melalui Media Sosial Facebook - Taka, Elvira Leonita; Andung, Petrus Ana; Nope, Hotlif Arkilaus; Konradus, Blajan; Dupe, Frengky (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2025)
The border communities of Indonesia and Timor Leste present intriguing social and cultural phenomena. The social relations between these border communities in both countries remain strong due to kinship ties and historical proximity, despite being separated by national administrative boundaries. The aim of this study is to analyze the cross-cultural communication patterns of the Indonesia-Timor Leste border communities through Facebook social media and to explore the meanings attached to digital interactions on social media by these communities. This qualitative research adopts an interpretive paradigm, employing a media ethnography methodology. Data collection was carried out through observations and in-depth interviews with community members, including youth, women, and community leaders. The findings indicate that social media has brought about a transformation in cross-cultural communication within the border communities, where Facebook has "replaced" conventional communication that previously relied on physical visits for socio-cultural activities between the Indonesia-Timor Leste border populations. The border communities also perceive the use of Facebook as a space to strengthen kinship, preserve cultural identity, and support local border economic activities. However, this study also identifies negative impacts of Facebook use, such as disputes arising from misinterpretations in digital communication, which are often resolved through culturally-based conflict resolution mechanisms. Overall, this research demonstrates that social media not only functions as a communication tool but also as a cultural space in which the Indonesia-Timor Leste border communities maintain their connectivity, identity, and solidarity. ABSTRAK Masyarakat perbatasan Indonesia dan Timor Leste menyimpan fenomena sosial dan budaya yang menarik. Relasi sosial masyarakat perbatasan di kedua negara ini tetap terjalin erat karena adanya ikatan kekerabatan dan kedekatan historis, meskipun terpisah oleh batas administratif negara. Tujuan dari penelitian ini adalah menganalisis pola komunikasi antarbudaya masyarakat perbatasan Indonesia–Timor Leste melalui media sosial Facebook dan mengeksplorasi makna yang dilekatkan masyarakat perbatasan terhadap interaksi digital di media sosial. Penelitian kualitatif ini menggunakan paradigma interpretatif, dengan metode etnografi media. Teknik pengumpulan data dilakukan melalui observasi, dan wawancara mendalam dengan masyarakat, termasuk pemuda, perempuan, dan tokoh masyarakat. Temuan penelitian menunjukkan bahwa media sosial telah membawa transformasi dalam komunikasi antarbudaya pada masyarakat perbatasan di mana Facebook “menggantikan” komunikasi konvensional yang mengandalkan kunjungan fisik untuk aktifitas sosial budaya di kalangan masyarakat perbatasan Indonesia-Timor Leste. Masyarakat perbatasan juga memaknai penggunaan Facebook sebagai ruang untuk memperkuat kekerabatan, mempertahankan identitas budaya, dan mendukung kegiatan ekonomi lokal perbatasan. Namun, penelitian ini juga menemukan dampak negatif dari penggunaan Facebook berupa perselisihan akibat salah tafsir dalam komunikasi digital, yang kerap diselesaikan melalui mekanisme penyelesaian konflik berbasis budaya. Secara keseluruhan, penelitian ini menunjukkan bahwa media sosial tidak hanya berfungsi sebagai alat komunikasi, tetapi juga sebagai ruang budaya di mana masyarakat perbatasan Indonesia-Timor Leste mempertahankan keterhubungan, identitas, dan solidaritas mereka.